Interweaving Assessment into Students’ Authentic Learning - Lu, Qingliang (Science Insights Education Frontiers, 2024)
Over decades, standardized testing has been the primary form of assessment of student learning. Standardized tests have been used as measurements of students’ knowledge retention, but with little capability of evaluating their capacities to apply knowledge in authentic contexts (Cai, 2000). With the advent of the information age, the limitations of conventional standardized tests have become increasingly pronounced. Assessment was one of the key concerns in the education reform in the 1990s. In the U.S., for example, America 2000: An Education Strategy emphasizes that measurements of student performance must be accurate, comparable, appropriate, and constructive; that placement decisions for young children should not be made on the basis of standardized tests; and that achievement tests must not simply measure minimum competencies, but also higher levels of reading, writing, speaking, reasoning, and problem-solving skills (Bush, 1991). Goals 2000: Educate America Act (1994) declares that its purpose is to provide a framework for meeting the National Education Goals by assisting in the development and certification of high-quality assessment measures that reflect the internationally competitive content and student performance standards, among other means.